Plataforma de prototipagem arduino no ensino da física: uma revisão sistemática da literatura - Maia Neto, Sebastião Costa (Universidade Federal Rural do Semi-Árido, 2020)
The teaching-learning process of Physics is the object of study for many academic works because it is considered a complex curricular component, which requires a certain ability to abstract formulas and concepts. In order to facilitate this process, the application of the Arduino prototyping platform has been implemented as a teaching tool. Due to the large number of existing methodological approaches, the mapping of methods of applying this technology in the classroom as well as the selection of which areas of Physics this application is pertinent to become time-consuming activities. Given this problem, this work presents a Systematic Literature Review (RSL), aiming at a bibliographic survey that determines similar studies, evaluating and defining an analysis of the application of the Arduino platform in Physics Education. Thus, a research protocol was defined with the necessary steps for the application of data extraction from the studies surveyed and with the classification of categories for the analyzed works. As a result of RSL, the qualitative research method and the comparative type validation were more addressed, that is, the works used the approach of development and reproduction of the experimental apparatus in the classroom. However, the use of several teaching methodologies, presented by the validation of Analysis and/or Experimental, was still noticed, even reduced. In this way, the results obtained at the end of this study suggest that the use of the Arduino Platform is adequate as a way to facilitate the teaching-learning stages in the teaching of Physics.
Keywords: Revisão sistemática da literatura; Arduino; Ensino da física; Systematic literature review; Arduino; Physics teaching; CIENCIAS EXATAS E DA TERRA::TECNOLOGIA DA INFORMACAO